Evaluation of Aerobic Exercise Induced Metabolic Stress on Serum Asprosin Levels: Comparison of Fitness Status - Algul, Sermin; Deniz, Gulnihal; Alp, Hamit Hakan; Ugras, Seda; Ozcelik, Oguz (Mattioli 1885, 2021)
We comparatively evaluated effects of aerobic exercise performed morning and afternoon on asprosin levels in young trained, sedentary males. A total of fifty male subjects (trained n=25, sedentary n=25) participated in morning and afternoon aerobic running exercises to approximately 70% of the subject's maximal heart rate for about 45 min. Pre- and post-exercise venous blood samples were taken and analysed for asprosin using ELISA. Serum CK and MDA levels were determined by measuring with an autoanalysers and a HPLC, respectively. Asprosin, CK and MDA levels increased significantly at the end of both morning (p<0.05), and afternoon (p<0.05) exercises in the trained and sedentary group. At the end of the acute running exercise in the trained group in the morning, the asprosine, MDA and CK levels increased by 24%, 29% and 32%; while they increased by 24%, 30%, and 40% in the afternoon, respectively. In the sedentary group, asprosin, MDA and CK levels increased by 31%, 38% and 31% after the acute running exercise in the morning, while the asprosin, MDA and CK levels increased by 34%, 58% and 42% after the acute running exercise in the afternoon, respectively. Asprosin levels increased in all subjects in both aerobic exercise tests without correlating increase of MDA and CK. Altered asprosin levels could be related other factors rather than metabolic and muscular stress parameters.
Keywords: Asprosin; Creatine Kinase; Exercise; Malondialdehyde; Metabolism